Angiotensin Converting Enzyme Gene Insertion/Deletion Polymorphism Is Not Responsible for Antihypertensive Therapy Induced New Onset of Type 2 Diabetes in Essential Hypertension. (January 2019) - Jhawat, Vikas; Gupta, Sumeet; Agarwal, Bimal K; Roy, Partha; Saini, Vipin
Background: Antihypertensive drug therapies have been reported to be associated with new onset of type 2 diabetes mellitus in some hypertensive patients after prolonged use. Angiotensin converting enzyme (ACE) gene has been found to affect essential hypertension, response of antihypertensive therapies, and glycemic disturbances. Therefore, ACE gene I/D polymorphism may be associated with risk of new onset of type 2 diabetes via metabolic disturbances, glycemic dysregulation, and insulin resistance. Aim: To assess the correlation between ACE gene I/D polymorphism and glycemic disturbance under influence of diuretic and other antihypertensive drug therapies. Materials and methods: We recruited 270 normotensive patients as control (150 men and 120 women), 270 hypertensive patients (95 men and 175 women), and 240 hypertensive with new onset of diabetes patients (80 men and 160 women). All samples were genotyped for ACE gene polymorphic alleles and relationship between different genotypes and anthropometric and clinical parameters along with drug therapies was established and analyzed. Results: Baseline clinical (systolic blood pressure, diastolic blood pressure, and fasting blood glucose level) and anthropometric parameters (height, weight, waist circumference, hip circumference, waist-hip ratio, and body mass index) of study populations were found highly statistically significant ( P < .05) when compared among study groups. Furthermore, genotype wise comparison of all these parameters in essential hypertensive (EH) and essential hypertensive with onset of diabetes (EHNOD) patients found most of them nonsignificant and no variation was found with respect to different genotypes of ACE gene. The genotype wise comparison of clinical parameters among different antihypertensive drug therapy was found statistically nonsignificant in both EH and EHNOD patients. Discussion: Anthropometric parameters can be taken as the risk indicator factors for hypertension and diabetes. However, ACE gene polymorphism may not be a risk factor for development of diabetes in hypertensive patients. Conclusion: The present study suggested that ACE gene polymorphism did not show any significant association with the risk of new onset of diabetes in EH patients and more detailed studies with large population size are needed.